PELATIHAN-PENDAMPINGAN ICT BOOK BERBASIS AUGMENTED REALITY UNTUK PENGUATAN MANAJEMEN PEMBELAJARAN & KETERAMPILAN BAHASA INGGRIS GURU SDN 6 KARIMUNJAWA - Muh. Shofiyuddin; Erna Zumrotun; Nor Latifah; Wulan Sutriyani; Noor Azizah; Dhea Dwi Triyanti; Noviana Sari; Nihlatun Niswah (Universitas Mataram, 2025)
Karimunjawa as a leading marine tourism destination demands increased English language proficiency, both for teachers and students. Its location in the 3T (underdeveloped, frontier, and outermost) region faces challenges in access to educational technology and improving English language proficiency as a provision for the younger generation in facing global interactions. However, the implementation of English learning at SDN 6 Karimunjawa is still limited. The learning process tends to be conventional, with teachers using more lecture methods and textbooks without utilizing modern technology. The objective of this community service activity is to improve innovative learning management and English language skills through the implementation of Augmented Reality (AR)-based ICT Books for teachers at SDN 6 Karimunjawa. The methods used include socialization, training, technology application, as well as mentoring and evaluation. This activity was attended by 17 teachers and went well, where participants were introduced to the ABBI (Aku Bisa Berbahasa Inggris) book integrated with AR technology. The results of the training and mentoring showed that 88% of teachers stated that this program was very useful, 82% considered AR media capable of improving teaching creativity, and 76% felt that its use was relatively easy although they still needed further mentoring. The observation results showed an increase in teacher competence by 40–53% in the use of innovative media, the application of AR in vocabulary learning, and increased student interaction and engagement in the classroom. For students, the initial and final ability tests showed an average increase in vocabulary mastery of 24.4%, pronunciation 22.3%, and learning engagement 25%, indicating that AR-based ICT Book is effective in improving learning outcomes while creating a more active, enjoyable, and contextual learning atmosphere. The application of AR-based ICT Books successfully improved teachers' English language skills and pedagogical competence, and supported the achievement of SDGs point 4 (Quality Education) in producing superior human resources.